The Policy on The Development of Integrated Coastal and Livestock Area Based on Geospatial in East Kalimantan - Abdunnur, Abdunnur; Mayulu, Hamdi (Technium BioChemMed, 2021)
In term of ecologically and economically, a coastal area which has different spatial characteristics according to the land conditions has high potency to be developed as it has physical and geographic advantages that can be utilized as the center of community activities. The development in the livestock sector requires a database including geospatial information and statistic data as the reference in the decision-making of livestock development area as not all areas are potential. The livestock in the coastal area in East Kalimantan Province has the potency to be developed into a livestock development area as it has been supported by the availability of land and feed sources. Besides agricultural areas, the land ecosystem which is located in the coastal areas can also be utilized by communities to rear livestock such as beef cattle, buffalo, sheep, and goats. Livestock breeding in this location can role as an income substitution for communities and could be an alternative livelihood for fishermen who can not go fishing due to bad weather and high waves. That pattern is expected to become a new activity concept that can improve communities’ income and welfare to be more independent and productive.